Chapter 3: Renewable energy transition, demand for metals and resource curse effects - André Månberger (Edward Elgar Publishing, 2021)
Mitigating climate change will require large-scale changes to energy systems. Two examples are increased use of renewable energy resources and electrification of the transport sector. These changes increase demand for metals. This chapter looks into which metals are used in renewable energy technologies and why, how much is required to transition the global energy system and which countries hold these metal reserves. Reserves of many metals used in renewable energy technologies are more geographically concentrated than fossil fuels. The resource and export revenues from metals are, for most countries, not as high as current revenues for fossil fuel exporters when compared to the size of their respective economies. More research is required to assess the local impact from increased mining which could be substantial for local economies, societies and the environment.